The role of pelvic lymphocele in the development of early postoperative complications. Issue 37 (September 2018) - Neagoe, Octavian Constantin; Ionica, Mihaela; Mazilu, Octavian
Abstract : Abstract: With the increasing incidence of gynecologic malignancy, radical hysterectomy represents an important part of the adequate treatment of these patients. The pelvic lymphocele is a known side effect of pelvic and para-aortic lymphadenectomy. The aim of our study was to assess the role of the lymphocele in the development of early postoperative complications. A single-center, retrospective analysis between January 2000 and May 2017 revealed 1867 patients with cervical and endometrial cancer, treated through radical or modified radical hysterectomy and pelvic lymphadenectomy. Postoperative complications and the occurrence of pelvic lymphocele were evaluated. Approximately 47.6% of patients were diagnosed with pelvic lymphocele, with only 5.2% being symptomatic. Early postoperative complications rate recorded an incidence of 8.1%, occurring more frequent if lymphocele were present ( P  < .001). The pelvic lymphocele represented, in univariate analysis, a risk factor for the development of pelvic abscesses, but not for deep vein thrombosis, lymphedema, or bowel obstruction. Hydronephrosis was found to be significantly correlated with the pelvic lymphocele, but we believe this urological complication to have a different underlining mechanism. Neoadjuvant radiotherapy represented in both uni- and multivariate analysis a risk factor for the occurrence of postoperative complications. In the postoperative context of oncogynecological surgery, pelvic lymphocele occur at high rates, representing a statistical risk factor for hydronephrosis and pelvic abscesses, with neoadjuvant radiotherapy being an independent risk factor for early postoperative complications.